Evaluation of Bronchoalveolar Lavage Cytology and Comparison with Endobronchial Biopsy - Acharya, Subarna; Yogi, Shubash (Journal of Nepalgunj Medical College, 2023)
Introduction: Early diagnosis of infective etiology and lung cancer plays a vital role in reducing mortality rate of lower respiratory tract disease. Different modalities can be applied for early diagnosis e.g. bronchoalveolar lavage and endobronchial biopsy. Cytological and histopathological diagnostic techniques are safer, economical and provide appropriate results. Aims: To find out diagnostic yield of bronchoalveolar lavage cytology in diagnosing lung pathology and to determine its sensitivity, and specificity in malignant cases considering endobronchial biopsy as the gold standard. Methods: This hospital based analytical study was carried out in the Department of Pathology at Nepalgunj medical college, Nepalgunj during the period from January 2023 to September 2023 with a total of 50 participants. Results: 29(58%) patients were male and 21(42%) female; the mean age was 53.16 ± 19.9 years. Considering histopathological findings, maximum patients of malignant cases had squamous cell carcinoma 3(6%), then adenocarcinoma 1(2%). The sensitivity, specificity, positive and negative predictive value of bronchoalveolar lavage in malignant cases were 75%, 100%, 100% and 50% respectively. Conclusion: Bronchoalveolar lavage fluid cytology is a useful tool for diagnosis of lung cancer. It has good sensitivity, and specificity, and shows nearly identical information as biopsy.